Investigating students’ online exam anxiety and culture on self-efficacy - Nurdian Susilowati; Lyna Latifah; Amir Mahmud; Ida Nur Aeni; Puji Novita Sari (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2022)
This study was aimed to examine the moderating role of coping strategy in online exam anxiety and culture on students’ self-efficacy. The research population was the students of Faculty of Economics who have taken two years of online learning and online exam. By using the proportionate random sampling technique, the research sample of 228 students. The data collected using a questionnaire were analysed using Moderated Regression Analysis (MRA). The results show that coping strategy weakened the relationship between anxiety and student self-efficacy during online exams. On the other hand, coping strategy can strengthen the relationship between culture and self-efficacy. In managing coping strategy, students pay attention to function-problem-focused coping and emotion-focused coping. Function-problem-focused coping is the ability of individuals to focus on solving the stress problems they experience during the exam. Emotion-focused coping is the ability of individuals to focus on managing their emotions during online exams. Self-efficacy in online exams (in the context of learning outcomes assessment) need to be studied in more detail.